A method of determination of the start and end of combustion in a direct injection diesel engine using the net heat release rate - Reyes, Joseph Gerard T. (Philippine Engineering Journal)
Biodiesels have been reported to produce higher amounts of NOx and other regulated emissions as opposed to neat diesel. The use of biofuels in the Philippines is mandated by Republic Act 9467. Concurrently, RA 8749 regulates, among other sources, emissions of compression ignition engines. This necessitates further analysis on the use of biodiesel blends in conventional diesel engines in order to check conformance with both laws. With the country recently acquiring a sophisticated engine test facility, users need to be given procedures in order to facilitate their investigations. Studies suggest that the amount of biodiesel emissions are related to ignition delay and combustion duration of diesel engines due to engine system response to the properties of biodiesels. Ignition delay is the duration in crank angle from the start of injection (SOI) of fuel into the engine cylinder until the start of combustion (SOC) of the fuel-air mixture. The combustion duration is the duration in crank angle bounded SOC and end of combustion (EOC). For compression-ignition engines, such as diesel engines, several approaches were developed and utilized in order to pinpoint the crank angle for the SOI, SOC and EOC. Some of these approaches required the use of specialized and dedicated equipment that would be found only in facilities that could afford to acquire them. Other methods estimated SOC using maximum of the 2nd or 3rd order derivatives of recorded in-cylinder pressures. These pressure data may also be utilized together with the corresponding cylinder volumes to generate the net heat release rate (NHRR), which shows the trend of heat transfer to the gases enclosed in the engine cylinder. The start of combustion is then determined at the point where the value of the NHRR is minimum and followed by a rapid increase in value, whereas the EOC is at the crank angle where the NHRR becomes zero prior to the exhaust stroke of the engine. In this study, a method of determining SOI, SOC and EOC was developed using injection line and in-cylinder pressures data recorded from tests of a common rail direct injection diesel engine. This proposed method was then matched against two distinct test criteria for SOC to test its feasibility and results have shown conformance to the two criteria.